Age-induced excellence with green solvents: the impact of residual solvent and post-treatments in screen-printed carbon perovskite solar cells and modules - Carys Worsley (Materials Advances, 2024)
Printable mesoscopic carbon perovskite solar cells (CPSCs) are cited as a potential frontrunner to commercialisation, as they are fabricated using low-cost screen printing. CPSCs produced using different perovskite precursor solvents benefit from different post-treatments. For example, cells made with DMF/DMSO precursors improve with light exposure, whereas γ-butyrolactone cells require humidity exposure for peak performance. Understanding the evolution of devices fabricated using different systems is therefore key to maximising PCE. This work examines the performance evolution of CPSCs and modules fabricated with low toxicity γ-valerolactone based precursors. It is found that PCE improves independently of humidity or light exposure due to gradual residual solvent loss and associated crystal realignment in the days following fabrication. In 1 cm2 cells significant Voc and FF produced an average increase of ∼15% on initial PCE, with some devices nearly doubling in performance. Similarly, 220 cm2 modules were also found to experience PCE increases. Critically, it appears this ageing step is essential for peak performance, as early encapsulation and extended heating impaired both performance and stability. This work may therefore help inform future work designing scaled-up processes for fabricating and encapsulating high performing CPSC modules.